2022
DOI: 10.7759/cureus.26209
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Androgen Deprivation Therapy in Prostate Cancer Patients: A Systematic Review

Abstract: The purpose of this study was to investigate the relationship between androgen deprivation therapy (ADT) and cardiovascular events in men with prostate cancer. Cardiovascular disease (CVD) is a primary cause of noncancer mortality in men with prostate cancer. Surveillance, Epidemiology, and End Results (SEER) Medicare-linked data revealed that CVD was responsible for about a quarter of deaths among men with prostate cancer, with a focus on the role of ADT as a contributing cause.We performed a literature searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moreover, in this current study, we observed a positive correlation between coronary heart disease and Vimentin in PC. This could be explained by the association of cardiovascular diseases and PC (Kakarla et al, 2022), and by the involvement of Vimentin in increasing stiffness, contractility, and endothelial dysfunction in arteries (Langlois et al, 2017). Furthermore, we found a positive correlation between E‐cadherin and β‐catenin, and a negative expression between the latter two markers and Vimentin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this current study, we observed a positive correlation between coronary heart disease and Vimentin in PC. This could be explained by the association of cardiovascular diseases and PC (Kakarla et al, 2022), and by the involvement of Vimentin in increasing stiffness, contractility, and endothelial dysfunction in arteries (Langlois et al, 2017). Furthermore, we found a positive correlation between E‐cadherin and β‐catenin, and a negative expression between the latter two markers and Vimentin.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of the use of GnRH agonists is the protection of ovarian reserve that was observed with the use of goserelin during chemotherapy, even though the exact mechanism has not been fully elucidated yet [ 112 ]. The impact of GnRH agonists on ischemic heart disease has not been established, but some authors report an increased risk of cardiovascular toxicity after treatment with GnRH agonists, especially in men with prostate cancer [ 113 , 114 ], whereas it has not been demonstrated in women with BC. A recent study found that female patients with breast cancer receiving GnRH agonists had a lower risk of developing ischemic heart disease than patients not receiving them [ 115 ].…”
Section: Breast Cancer Therapiesmentioning
confidence: 99%
“…However, adverse drug effects are common with these hormonal therapies and may vary with patient and drug characteristics [10,11]. Furthermore, cardiovascular disease (CVD) is a primary cause of noncancer mortality in men with prostate cancer [12]. A recent study identified that CVD accounted for almost 30.2% of all deaths among prostate cancer patients [13].…”
Section: Introductionmentioning
confidence: 99%